Lycoris ‘Tao Hong’: A New Ornamental Lycoris Hybrid Cultivar - Yang, Shaoqin; Li, Zuohui; Fu, Li; Zheng, Yuhong; Huang, Ye; Zhang, Pengchong (HortScience, 2023)
The genus Lycoris Herb. belongs to the Amaryllidaceae family, which consists of about 20 species and is distributed in warm temperate to subtropical zones of East Asia, from southwestern China to Japan and southern Korea, with a few zones extending to northern Indochina and Nepal. The species is easy to hybridize with each other, and more than half of the currently recognized taxa are certainly of hybrid origin (Hsu et al. 1994; Ji and Meerow 2000; Tsi and Meerow 2000). In recent years, with the in-depth development of field investigation and taxonomic research, many new species have been published successively. Up to now, more than 30 species have been named legally, of which more than 20 are endemic to China (Li et al. 2022; Lu et al. 2020; Meng et al. 2018; Quan et al. 2013; Zhang et al. 2021). Lycoris has its specific traits and benefits. When they bloom from summer to fall, when others are not active, the stems are leafless, with an inflorescence at the top containing four to eight flowers. These flowers are characterized by their pastel, plentiful colors, and multiple flower shapes (Hsu et al. 1994). Because of the special flower shape and biological habit, they have common names such as spider lily, surprise lily, hurricane lily, and magic lily. Moreover, the bulbs of Lycoris have been used in traditional Chinese medicine, as some Amaryllidaceae alkaloids isolated from the bulbs of Lycoris have been reported to exhibit immunostimulatory, antitumor, antiviral, and antimalarial activity (Wang et al. 2013). With an increasing demand for Lycoris as a commercial horticultural product, the breeding of different varieties with new petal forms and/or colors has become a valued necessity for Lycoris (Yang et al. 2021). This new cultivar is a natural hybrid population between Lycoris radiata and Lycoris aurea, which has a unique red-pink color, taller stem, and bigger flower, making it more beautiful and suitable for landscaping and cut flowers.